2013
DOI: 10.1007/s12013-012-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells

Abstract: Diabetic cardiomyopathy has been shown to promote hypertrophy, leading to heart failure. Recent studies have reported a correlation between diabetic cardiomyopathy and oxidative stress, suggesting that the accumulation of advanced glycation end products (AGEs) induces the production of reactive oxygen species (ROS). In a clinical setting, AGEs have been shown to increase the risk of cardiovascular disease; however, the relationship between AGEs and cardiac hypertrophy remains unclear. This study sought to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…However, the role of AGEs in the pathogenesis of diabetic cardiomyopathy remains unclear. Findings in our previous study suggest that AGEs regulate ERK phosphorylation via ROS [40]. In the current report, we provide additional evidence to support the contention that AGEs are closely associated with the pathogenesis of diabetic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the role of AGEs in the pathogenesis of diabetic cardiomyopathy remains unclear. Findings in our previous study suggest that AGEs regulate ERK phosphorylation via ROS [40]. In the current report, we provide additional evidence to support the contention that AGEs are closely associated with the pathogenesis of diabetic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 85%
“…It has been demonstrated that MEK/ERK promotes cardiac hypertrophy in transgenic mice [56], which is a characteristic of diabetic cardiomyopathy [57,58]. Our previous study demonstrated that AGEs regulate ERK phosphorylation via ROS and induce cell hypertrophy [40]. The results obtained in the current study demonstrate that AGEs and H 2 O 2 increase ERK phosphorylation; however, the effects of AGEs are inhibited by pretreatment with NAC or PD98059.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Consistent changes of hypertrophy and ERK1/2 expressions were also observed in STZ-induced myocardium of diabetic rats [62]. It is believed that ERK1/2 activation in response to hyperglycemia results in cardiac hypertrophy [63,64]. …”
Section: Erk1/2 a Two-edged Sword In Dcm Developmentmentioning
confidence: 90%